Objective questions in library and information science - Ghante,P.B (Ess Ess, 2013)
This book is for students in the field of library and information science in India, who must qualify for the National Eligibility Test (NET) for lectureship and the Junior Research Fellowship (JRF) Examination, being conducted by India's University Grants Commission. The book will benefit all those seeking a Bachelor's degree, Master's degree, M. Phil., or Ph.D in library and information science. Additionally, the book will assist those seeking a position in a large number of prestigious organizations and national level institutions, such as India's Public Service Commission, the Delhi Administration, the Staff Selection Commission, etc.